(untitled) (Journal of Mechanical Engineering, 2016)
Water-in-glass evacuated tube solar collectors are widely used in two main configurations: (1) a single row of tilted tubes connected to a header tank, and (2) two rows of horizontal tubes on either side of a central manifold. Published studies on water-in-glass collectors have been focused almost entirely on the former, commonly used for domestic water heating applications. This study considers the latter type, which is well suited to larger solar water heating applications. Experimental data from outdoor testing demonstrates a good fit to the ISO 9459-2 expression for collector performance. This daily heat gain model is used in simulations to illustrate sizing and design applications.